SURAH HUJRAT’s REFORMATIVE RELIGIOUS AND SOCIAL THEMES/ SUBJECTS FOR MANKIND - Dr. Waleed Khan; Dr. Talib Ali Awan; Fakhra Tahseen (Al Manhal Research Journal, 2023)
The surah is madinan and surah takes its name from verse 4 in which the word hujrat has occurred. Surah is collection of the commandments and instructions sent down on different occasions. The themes/ subjects of this surah are to teach the muslims regarding manners worthy of true believers. In the first five verses they have been taught the etiquettes they should observe with regard to ALLAH Almighty (Subhana Hu Wa Ta’ala) and His Messenger (Peace Be Upon Him). Then, Muslims have been given instructions that it is not right to believe in every news blindly and to act accordingly, without due thought. Then, it has been told what attitude the other Muslims should adopt in case two groups of the Muslims falls to mutual fighting. Then, the muslims have been instructed to safe guard against the evils of life, mocking, taunting, calling other with nicknames, creating suspicion, spying others and back biting. ALLAH Almighty (Subhana Hu Wa Ta’ala) has mentioned all these evils separately and forbidden them as unlawful. After this, the national and racial distinctions that causes universal corruption have been condemned. ALLAH Almighty (Subhana Hu Wa Ta’ala) in a brief verse has cut at the root of this evil by stating “All human beings are descendants of the same one pair and there are no lawful basis of one man’s superiority over the others except on the basis of moral excellence”. At the end, the people have been told that the real thing is not the verbal profession of the Faith but to believe in ALLAH Almighty (Subhana Hu Wa Ta’ala) and his Messenger truly.